ANALISIS PERLAKUAN AKUNTANSI ATAS PENGELOLAAN BERAS SEJAHTERA PADA PERUM BULOG DIVRE SULAWESI UTARA DAN GORONTALO - Imbang, Veronika Merlin; Pontoh, Winston; Gamaliel, Hendrik (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
The Beras Sejahtera (Rastra), a program that assisted by government, has been working with Public Enterprise Logistics Company (Perum Bulog) in an attempt to improve food security as well as provide protection for underprivileged communities. This research aims to know the accounting of the management of the Beras Sejahtera at Perum Bulog Divre North Sulawesi and Gorontalo. The methods used in this research is descriptive method and qualitative research. This research obtained that the accounting Â of the management of the Beras Sejahtera at Perum Bulog Divre North Sulawesi and Gorontalo is using accrual-based and the reports are already organized in the regulation of Director Of Public Companies On Accounting Policy in Perum Bulog.Keywords: Analysis, Accounting, Beras Sejahtera